2014
DOI: 10.1128/aac.02094-13
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Cell-Based Hepatitis C Virus Infection Assay for Quantitative High-Throughput Screening of Anti-Hepatitis C Virus Compounds

Abstract: bTherapy for hepatitis C virus (HCV) infection has advanced with the recent approval of direct-acting antivirals in combination with peginterferon and ribavirin. New antivirals with novel targets are still needed to further improve the treatment of hepatitis C. Previously reported screening methods for HCV inhibitors either are limited to a virus-specific function or apply a screening method at a single dose, which usually leads to high false-positive or -negative rates. We developed a quantitative high-throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 46 publications
(60 reference statements)
1
42
0
Order By: Relevance
“…We confirmed that this class of inhibitors interferes with viral entry of different HCV genotypes (Fig. 5) using as a representative member of the group perphenazine, which has also been recently identified as an HCV inhibitor by others (34). We have also reported previously that dibenzazepines inhibit HCV entry (12).…”
Section: Discussionsupporting
confidence: 85%
“…We confirmed that this class of inhibitors interferes with viral entry of different HCV genotypes (Fig. 5) using as a representative member of the group perphenazine, which has also been recently identified as an HCV inhibitor by others (34). We have also reported previously that dibenzazepines inhibit HCV entry (12).…”
Section: Discussionsupporting
confidence: 85%
“…Alternatively, there may be subtle strain-specific differences regarding the membrane requirements to trigger fusion, and the resistance mutations observed may change these requirements. Either way, it is enigmatic that HCV pseudoparticles (HCVpp), i.e., retroviral particles carrying the HCV envelope proteins E1 and E2 at their surfaces (50,51), in contrast to authentic cell culture-derived HCV particles (HCVcc) with exactly the same glycoproteins, are not inhibited by flunarizine (5,7,52). Moreover, chlorcyclizine inhibits HCVcc but not HCVpp (6).…”
Section: Ion Channel Inhibitors and Related Antihistamines As First-imentioning
confidence: 99%
“…31 This technological advance led to the large-scale screening of compound libraries and the identification of potential therapeutics. Our group and others recently published reports identifying antihistamine chlorcyclizine HCl (CCZ) as a potent inhibitor of HCV replication.…”
Section: Emerging Therapies With Compounds Having An Unknown Mechanismentioning
confidence: 99%